Acute Right Ventricular Failure: Pathophysiology, Diagnostic Approach with Emphasis on the Role of Echocardiography - Tun, Han N.; Almaghraby, Abdallah; Kavalerchyk, Vladyslav; Muraru, Denisa; Soliman-Aboumarie, Hatem; Abdelnabi, Mahmoud (Current Cardiology Reviews, 2023)
Right ventricular function is one of the important predictors of survival in heart failure patients. In the past, there has been only limited knowledge regarding right-sided heart failure when compared to left-sided failure. However, there are more emerging data in recent years, and several studies have emphasized the unique features of the right ventricle regarding its anatomy, pathophysiology, clinical consequences, diagnostic modalities, and treatment options. Despite that, management of acute right ventricular failure is still challenging. This article summarizes an overview of acute right heart failure including pathophysiology, causes, clinical features, and diagnostic work-up with emphasis on the role of echocardiography.
Keywords: prognosis